Design Optimization and In Vitro-In Vivo Evaluation of Orally Dissolving Strips of Clobazam - Bala, Rajni (Hindawi Publishing Corporation, 2014)
Clobazam orally dissolving strips were prepared by solvent casting method. A full 3(2) factorial design was applied for optimization using different concentration of film forming polymer and disintegrating agent as independent variable and disintegration time, % cumulative drug release, and tensile strength as dependent variable. In addition the prepared films were also evaluated for surface pH, folding endurance, and content uniformity. The optimized film formulation showing the maximum in vitro drug release, satisfactory in vitro disintegration time, and tensile strength was selected for bioavailability study and compared with a reference marketed product (frisium5 tablets) in rabbits. Formulation (F6) was selected by the Design-expert software which exhibited DT (24 sec), TS (2.85 N/cm(2)), and in vitro drug release (96.6%). Statistical evaluation revealed no significant difference between the bioavailability parameters of the test film (F6) and the reference product. The mean ratio values (test/reference) of C (max) (95.87%), t (max) (71.42%), AUC(0−t) (98.125%), and AUC(0−∞) (99.213%) indicated that the two formulae exhibited comparable plasma level-time profiles.